Cryogenic optical localization provides 3D protein structure data with Angstrom resolution - Weisenburger, Siegfried; Boening, Daniel; Schomburg, Benjamin; Giller, Karin; Becker, Stefan; Griesinger, Christian; Sandoghdar, Vahid (Nature methods, 2017)
We introduce Cryogenic Optical Localization in 3D (COLD), a method to localize multiple fluorescent sites within a single small protein with Angstrom resolution. We demonstrate COLD by determining the conformational state of the cytosolic Per-ARNT-Sim domain from the histidine kinase CitA of Geobacillus thermodenitrificans and resolving the four biotin sites of streptavidin. COLD provides quantitative 3D information about small- to medium-sized biomolecules on the Angstrom scale and complements other techniques in structural biology.
EAM Import::2019-03-13

Mechanism of sensor kinase CitA transmembrane signaling - Zhang, Xizhou Cecily; Xue, Kai; Salvi, Michele; Schomburg, Benjamin; Mehrens, Jonas; Giller, Karin; Stopp, Marius; Weisenburger, Siegfried; Böning, Daniel; Sandoghdar, Vahid; Unden, Gottfried; Becker, Stefan; et al. (Nature Communications, 2025)
Membrane bound histidine kinases (HKs) are ubiquitous sensors of extracellular stimuli in bacteria. However, a uniform structural model is still missing for their transmembrane signaling mechanism. Here, we used solid-state NMR in conjunction with crystallography, solution NMR and distance measurements to investigate the transmembrane signaling mechanism of a paradigmatic citrate sensing membrane embedded HK, CitA. Citrate binding in the sensory extracytoplasmic PAS domain (PASp) causes the linker to transmembrane helix 2 (TM2) to adopt a helical conformation. This triggers a piston-like pulling of TM2 and a quaternary structure rearrangement in the cytosolic PAS domain (PASc). Crystal structures of PASc reveal both anti-parallel and parallel dimer conformations. An anti-parallel to parallel transition upon citrate binding agrees with interdimer distances measured in the lipid embedded protein using a site-specific 19F label in PASc. These data show how Angstrom scale structural changes in the sensor domain are transmitted across the membrane to be converted and amplified into a nm scale shift in the linker to the phosphorylation subdomain of the kinase.
CRIS-Team Scopus Importer:2025-02-14

Three-dimensional angstrom resolution in fluorescence microscopy: Insight into protein structure - Boening, Daniel; Weisenburger, Siegfried; Schomburg, Benjamin; Giller, Karin; Becker, Stefan; Griesinger, Christian; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2023-03-27